Social Workers’ Choice Making in Supporting Nature Activities by Parents and Children in Shelters - Peters, Elise; Hovinga, Dieuwke; Maas, Jolanda; Schuengel, Carlo (Frontiers in Psychology, 2022)
Visiting a natural environment such as a garden or park helps people to recover from stressful circumstances. Women’s shelters and homeless shelters have started to integrate nature in their work, especially for families who seek temporary refuge, with the aim to support parents’ functioning and resilience. For professionals who want to facilitate engagement with nature among their clients, it may be helpful to learn how other professionals choose nature activities for the support of parents. The current study was aimed to uncover how social workers choose a nature activity for the support of parents, resulting in a model that can be used as a reflective tool among shelter professionals. The model is based on an analysis of actions of professionals, captured in case descriptions written by shelter professionals about parenting supportive nature activities that they facilitated for families under their care. The model shows that social workers promoted a back-and-forth between children’s exploration away from the parent and being with the parent. In facilitating these interactions, social workers used nature as an environment with stress reducing and strengthening capacities for parents and as an environment with supportive qualities for children's play. A dimensional framework was extracted that described how professionals may choose activities.